Five new southeastern Brazilian Myrtaceae - Sobral, Marcos; Mazine, Fiorella F.; Leoni, Lúcio; Souza, Marcelo C.; Melo, Eugênio A.d. (Phytotaxa, 2016)
We describe, illustrate and compare with related species the southeastern Brazilian Calyptranthes arachnicola, C. biconvexa, C. carangola, Eugenia grandissima and Plinia longa. Calyptranthes arachnicola, from the state of Rio de Janeiro, is apparently related to Calyptranthes ursina, differing by its larger blades and pendulous inflorescences; Calyptranthes biconvexa, also from Rio de Janeiro, is apparently related to C. lanceolata, being distinguished by its blades with adaxially biconvex midvein and shorter inflorescences; Calyptranthes carangola, from the state of Minas Gerais, is apparently close to C. curta, differing by its narrower blades, longer inflorescences and narrower bracts; Eugenia grandissima, also from Minas Gerais, is apparently close to E. umbrosa, but has larger leaves and petioles, blades with midvein adaxially raised and larger bracteoles; and Plinia longa, from the state of Espírito Santo, is related to Plinia edulis, differing by its narrowly oblong leaves. Additionally, species are evaluated for their conservation status according to the information available.